Legal Analysis of User Personal Data Leak Cases at Tokopedia - Elfian Fauzy,; Annisa Hafizhah, (Mahadi: Indonesia Journal of Law, 2023)
The rapid development of technology has facilitated various aspects of human life, including in conducting various buying and selling transactions online through marketplaces such as Tokopedia which has the position as the marketplace with the largest value in Indonesia. However, in 2020 Tokopedia experienced a case of personal data leakage, around 91 million Tokopedia user account data was hacked which was sold on the dark web at a price of 5000 dollars. Regarding this incident, the Indonesian Consumer Community, chaired by David Tobing, then filed a lawsuit against PT Tokopedia and the Ministry of Communication and Informatics at the Central Jakarta District Court. Unfortunately, at that time Indonesia did not have a dispute resolution mechanism for cases of leakage of personal data protection and did not yet have a Personal Data Protection Act, so it was very difficult to carry out the trial process. Therefore, the problem in this paper is: How is the Legal Analysis of Leakage Cases of Users' Personal Data on Tokopedia? This paper is normative research that uses primary and secondary legal sources. Data collection was carried out through literature study and all data collected was then analyzed qualitatively. In the end, the Judge through Interlocutory Decision has decided to reject the lawsuit. In the interlocutory decision, the Judge decided on three matters, namely: 1. Declared that the exceptions of the Defendants were accepted and granted; 2. Declare that the District Court has no authority to try the “a quo“ case; and 3. Ordering the Plaintiff to pay court costs in the amount of Rp 516,000.